(untitled) (World Economics and Finance Bulletin, 2025)
This research deals with the suspicion of "Imam Hussein throwing himself into destruction" that was raised about his uprising against the Umayyad rule in the year 61AH, a suspicion through which some sought to cast doubt on the legitimacy of his revolution and its goals. Some of them linked Imam Hussein’s uprising against Caliph Yazid bin Muawiyah with the concept of "throwing oneself into destruction" mentioned in the Holy Quran, where they interpreted his departure as a reckless act that exposed himself to destruction without a legitimate justification. However, this understanding ignores the deep and legitimate dimensions of Imam Hussein’s position, which was based on lofty principles and profound beliefs, as his main goal was to revive Islamic values and defend the religion of God against the deviations that the Islamic community witnessed under the Umayyad rule. The research aims to dismantle this suspicion by providing a precise analysis of the legal texts such as the Qur’anic verses and the Prophetic hadiths that can contribute to clarifying the position of Imam Hussein, as well as by relying on the rational principles that govern his actions. The research shows how the Husseini uprising was not a throwing of oneself into destruction, but rather a challenge to injustice and tyranny. Through this, it seeks to highlight the moral and human dimensions of the revolution, which did not aim at destruction, but rather at a radical change in the Islamic reality